Features of monitoring systems of information sizable streams - Луценко, Володимир Миколайович; Балан, Андрій Миколайович (Ukrainian Information Security Research Journal, 2013)
The analysis is necessary for construction of complex systems of protection of die information and other systems of safety to risk. At service of systems of sizable data transmission in optical communication lines supervision over the information is a complicated problem. It demands application of new hardware decisions in means of die control and data gathering which are initial information base of die future projects. The problem of use of new means of protection of the information is considered at designing complex systems of protection of die information. The main attention is given a quality monitoring for streams of the information of the big size, and which are accessible to attacks Cybernetic criminals. Questions used on die markets of Ukraine and behind its limits of such monitoring systems which functionalities allow to solve tasks of protection from Cybernetic terrorism at their use as means of protection of die information widiin die framework of projects systems of complex of protection are considered.